Perinatal characteristics and retinoblastoma - Heck, Julia E (2012)
PURPOSE: The etiology of retinoblastoma remains poorly understood. In the present study, we examined associations between perinatal factors and retinoblastoma risk in California children. METHODS: We identified 609 retinoblastoma cases (420 unilateral, 187 bilateral, and 2 with laterality unknown) from California Cancer Registry records of diagnoses 1988–2007 among children <6 years of age. We randomly selected 209,051 controls from California birthrolls. The source of most study data was birth certificates. Multivariable logistic regression was used to examine associations between retinoblastoma and perinatal characteristics. RESULTS: Bilateral retinoblastoma was associated with greater paternal age [for fathers over 35, crude Odds Ratio (OR)=1.73, 95% Confidence Interval (CI) 1.20, 2.47] and with twin births (OR=1.93, 95% CI 0.99, 3.79). Among unilateral cases, we observed an increased risk among children of US-born Hispanic mothers (OR=1.34, 95% CI 1.01, 1.77) while a decreased risk was observed for infants born to mothers with less than 9 years of education (OR=0.70, 95% CI 0.49–1.00), a group that consisted primarily of mothers born in Mexico. We observed that maternal infection in pregnancy with any STD (OR=3.59, 95% CI 1.58, 8.15) was associated with bilateral retinoblastoma. CONCLUSIONS: This study supports the findings of previous investigations reporting associations between parental age, HPV infection and retinoblastoma.